1970
DOI: 10.1111/j.1745-3984.1970.tb00699.x
|View full text |Cite
|
Sign up to set email alerts
|

FLUENCY AS A PERVASIVE ELEMENT IN THE MEASUREMENT OF CREATIVITY1

Abstract: It was suggested that fluency, defined as number of responses, may misleadingly influence both high Intercorrelations sometimes reported among measures of creativity and low correlations sometimes reported between measures of creativity and intelligence. Subjects were 93 Saturday art school students between the ages of 9 and 15 years. Intercorrelations among five “creativity” scores derived from a slightly modified version of Torrance's Figure Completion Test and between these scores and Henmon‐Nelson Intellig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
3

Year Published

1973
1973
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 5 publications
1
50
0
3
Order By: Relevance
“…Many variations of uniqueness scoring have been proposed, such as weighting each response by its frequency (Runco, Okuda, & Thurston, 1987), scoring only the first three responses (Clark & Mirels, 1970), or quantifying fluency as the number of non-unique responses (Moran, Milgram, Sawyers, & Fu, 1983). Although worthwhile attempts, these scoring methods have not always performed well psychometrically (Michael & Wright, 1989;Speedie, Asher, & Treffinger, 1971).…”
Section: Uniqueness Scoring Confounds Fluency and Creativitymentioning
confidence: 99%
See 1 more Smart Citation
“…Many variations of uniqueness scoring have been proposed, such as weighting each response by its frequency (Runco, Okuda, & Thurston, 1987), scoring only the first three responses (Clark & Mirels, 1970), or quantifying fluency as the number of non-unique responses (Moran, Milgram, Sawyers, & Fu, 1983). Although worthwhile attempts, these scoring methods have not always performed well psychometrically (Michael & Wright, 1989;Speedie, Asher, & Treffinger, 1971).…”
Section: Uniqueness Scoring Confounds Fluency and Creativitymentioning
confidence: 99%
“…Since the 1970s, researchers have discussed the fluency confound as a problem and have considered ways of handling it (Clark & Mirels, 1970;Dixon, 1979;Hocevar, 1979aHocevar, , 1979bHocevar & Michael, 1979). Many variations of uniqueness scoring have been proposed, such as weighting each response by its frequency (Runco, Okuda, & Thurston, 1987), scoring only the first three responses (Clark & Mirels, 1970), or quantifying fluency as the number of non-unique responses (Moran, Milgram, Sawyers, & Fu, 1983).…”
Section: Uniqueness Scoring Confounds Fluency and Creativitymentioning
confidence: 99%
“…Se tomó la decisión de utilizar una originalidad media para controlar el efecto de confluencia de la variable fluidez de la que se habla en la literatura (Clark & Mirels, 1970;Hocevar & Michael, 1979;Mouciroud & Lubart, 2001;Primi et al, 2013;Runco & Marz, 1992;Silvia, Martin & Nusbaun, 2009). …”
Section: C) Obtención De La Variable Originalidadunclassified
“…The first problem is that uniqueness scores are highly correlated with fluency scores. Researchers pointed this out soon after Wallach and Kogan (1965) published their landmark tasks and scoring methods (e.g., Clark & Mirels, 1970), and later research further demonstrated that uniqueness and fluency are essentially confounded (Hocevar, 1979a, Hocevar, 1979band Hocevar and Michael, 1979. This confounding is apparent even in the field's "gold standard" samples.…”
Section: Uniqueness Scoringmentioning
confidence: 99%